A cross-sectional study of obesogenic behaviours and family rules according to family structure in European children - Katharina Stahlmann; Antje Hebestreit; Stefaan DeHenauw; Monica Hunsberger; Jaakko Kaprio; Lauren Lissner; Dénes Molnár; Alelí M. Ayala-Marín; Lucia A. Reisch; Paola Russo; Michael Tornaritis; Toomas Veidebaum; et al. (BMC, 2020)
Abstract Background There has been an increase in children growing up in non-traditional families, such as single-parent and blended families. Children from such families have a higher prevalence of obesity and poorer health outcomes, but research on the relationship with obesogenic behaviours is limited. Objectives Therefore, the aim of this study was to investigate whether there are associations between family structures and obesogenic behaviours and related family rules in European children and adolescents. Methods The sample included 7664 children (mean age ± SD: 10.9 ± 2.9) from 4923 families who were participants of the multi-centre I.Family study (2013/2014) conducted in 8 European countries. Family structure was assessed by a detailed interview on kinship and household. Obesogenic behaviours (screen time, sleep duration, consumption of sugar-sweetened beverages (SSBs)) and family rules (rules for computer and television, bedtime routine, availability of SSBs during meals) were determined by standardized questionnaires. Multilevel mixed-effects linear and logistic regression models were used to model the associations of family structure with obesogenic behaviours and family rules. Sex, age, parental education level, number of children and adults in the household and BMI z-score were covariates in the models. Two-parent biological families were set as the reference category. Results Children from single-parent families were less likely to have family rules regarding screen time (OR: 0.62, 95% CI: 0.40-0.94, p = 0.026) with higher reported hours of screen time per week (β = 2.70 h/week, 95% CI: 1.39-4.00, p < 0.001). The frequency of weekly SSB consumption differed by family structure in a sex-specific manner: girls from single-parent (β = 3.19 frequency/week, 95% CI: 0.91-5.47, p = 0.006) and boys from blended/adoptive families (β = 3.01 frequency/week, 95% CI: 0.99-5.03, p = 0.004) consumed more SSBs. Sleep duration, bedtime routines and availability of SSBs during meals did not differ between children from these family structures. Parental education did not modify any of these associations. Conclusions Parents in non-traditional family structures appear to experience more difficulties in restricting screen time and the intake of SSBs in their children than parents in traditional two-parent family structures. Our findings therefore suggest that additional support and effective strategies for parents in non-traditional families may help to reduce obesogenic behaviours in children from such family types.